Artist/Executioner: Antidotes to Counter-Revolutions - Kim, Eunsong (The Nordic Journal of Aesthetics, 2025)
This essay examines Pat Parker’s unpublished and undated novel draft, “Assassination,” which follows two fictional characters, the journalist Jennifer Moore, as she investigates Tracy Scott, a former member of the Black Panther Party who assassinates the president after being appointed as the first director of “Race Relations.” “Assassination” delineates the intra-tensions between liberal and radical politics, honing in on journalist Moore’s fixation of how coverage of Scott’s actions will elevate her career, while refusing to tend to Scott’s revolutionary politics. Parker’s configuration of the liberal writer, who awaits the sacrifice of revolutionaries, speaks to the dynamics of violence in a counterrevolutionary society. I take up Parker’s examination of the liberal politics of the artist subject, and the ways writers collude with the counter-revolution by situating radical action and sacrifice as artistic fodder. Furthermore, I contend with how Parker composes a fictional landscape without innocence: the artist is compromised, and revolutionary action involves violence. This approach is in direct contrast to colonial narrations of victims and innocence. Taking up psychoanalyst Christopher Bollas’ notion of “violent innocence,” Christina Sharpe’s analysis of the enmeshment of whiteness and innocence in the media, Dionne Brand’s repudiation of the virtue of the poet subject, and Saidiya Hartman’s critiques of the corporatization of antiracist discourse in “Crow Jane,” the essay examines the aesthetic and political innovations offered in the rejection of colonial innocence.